2020
DOI: 10.31557/apjcp.2020.21.6.1755
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Chemotherapy with Methotrexate Leucovorin in High-Risk Hydatidiform Mole

Abstract: Aim: Gestational Trophoblastic Neoplasia (GTN) is used to describe a group of malignant gestational tumors originating from the placenta. The chance of having malignant GTN is high in a high-risk molar pregnancy. The main aim of this study is to investigate the effectiveness of using prophylactic chemotherapy in high-risk molar pregnancy to prevent malignant GTN. Method: In this case-control retrospective study, all patients with high-risk mole referred to Firoozgar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Mean age of participants in this study was about five years lower than two other studies conducted at Tehran and Ankara. [ 9 13 ] The Ankara study had 39% primigravid women, which is quite close to the present study. Pre evacuation β HCG level had wider dispersion in the Ankara study (minimum 551 mIU/ml- maximum 844,441 mIU/ml) compared to present study (22,918 to 360,000 mIU/ml) which can be attributed to the enrolment of both high-risk and low-risk CHM.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Mean age of participants in this study was about five years lower than two other studies conducted at Tehran and Ankara. [ 9 13 ] The Ankara study had 39% primigravid women, which is quite close to the present study. Pre evacuation β HCG level had wider dispersion in the Ankara study (minimum 551 mIU/ml- maximum 844,441 mIU/ml) compared to present study (22,918 to 360,000 mIU/ml) which can be attributed to the enrolment of both high-risk and low-risk CHM.…”
Section: Discussionsupporting
confidence: 89%
“…Reported time for spontaneous remission of β HCG was 3.2 ± 1.21 months and it was 2.5 ± 1.33 for women with high-risk CHM treated with methotrexate-leucovorin prophylactic CT.[ 9 ] Post evacuation β HCG values and NT as prognostic markers has been explored in several studies. A meta-analysis reports only 0.3% incidence of post-molar GTN following β HCG normalization in CHM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yamamoto et al [3] investigated 472 patients with high-risk CHM and found that gestational week, serum βHCG level at one week after the rst evacuation, and pathological remnants were signi cantly associated with the development of PGTN. Aminimoghaddam et al [20] divided 102 patients with high-risk CHM into two groups: recipients and non-recipients of MTX (Methotrexate 1mg/kg in the odd days (1,3,5,7) and leucovorin 0.1 mg/kg (IM) in the even days (2,4,6,8)). In the MTX recipient group, 13.7% of cases developed PGTN, while in the non-recipient group, 31.4% of cases developed PGTN (p-value: 0.03).…”
Section: Resultsmentioning
confidence: 99%